Requerimento do capitão-mor Inocêncio Moreira de Campos, morador em Macau, a [D. João IV], rei de Portugal, em que pede o Hábito de Cristo para si e para seu filho, com a pensão de setenta mil réis para cada um (1643)
This abstract describes a composite historical document originating from the Portuguese colonial administration in Asia, comprising a 1643 petition by Innocencio Vieira de Campos (Lisbon, 17 December), a 1646 ecclesiastical memorandum concerning Fr. Guedes’s appointment as *Doutor de Cristo* and *Concertador de Pensão* in Goa (24 January), and a 1680 Inquisitorial deposition by Gaspar de Faria Feuereiro—corrected from apparent scribal errors to 17 July 1640 and September 1680—relating to residence, age, lineage, and procedural compliance within the Holy Office’s jurisdiction in Lisbon and Goa. The text includes petitions for royal honours, pension entitlements, and ecclesiastical office; references to Macau, Goa, Lisbon, Malacca, Cannanore, Tanar (Tana), Mascate, and Manila; and documentation of military service (including the 1656 siege of Malacca and engagement with the Acehnese armada), fortification works, diplomatic missions to Chinese authorities, and Inquisitorial scrutiny of orthodoxy and canonical standing. Key figures include Jerusalém Vieira de Campos Couceiro, Gaspar de Faria Feuereiro, Fr. Guedes, and Inquisitor Father Pinto de Oraz. The document bears archival reference CLo. 17.8 and reflects administrative, military, ecclesiastical, and judicial practices of the Portuguese Estado da Índia and metropole across the seventeenth century.
Keywords: Composite Historical Document; Concertador de Pensão; Doutor de Cristo; Father Pinto de Oraz; Fr. Guedes; Gaspar de Faria Feuereiro; Goa; Innocencio Vieira de Campos; Jerusalém Vieira de Campos Couceiro; Lisbon; Macau; Malacca; Manila; Portuguese Colonial Administration in Macao; Portuguese Inquisition in Goa; Transcription